Review of Fatih Ermiş’, A History of Ottoman Economic Thought: Developments Before the Nineteenth Century - Sariyannis, Marinos (Historein, 2016)
Fatih Ermiş. A History of Ottoman Economic Thought: Developments Before the Nineteenth Century. London: Routledge, 2014.